Komunikasi Visual Manfaat Daun Kelor Bagi Kesehatan Gizi Anak Usia 7-12 Tahun Di Kota Palembang - Ulfa, Yulia; Patriansah, Mukhsin; Yulius, Yosef (Besaung : Jurnal Seni Desain dan Budaya, 2025)
Moringa leaves (Moringa oleifera) are very well known as a rich source of nutrition and are beneficial for children's health. These leaves contain lots of protein, vitamins, minerals and antioxidants which are important for optimal growth and development. The main benefits of moringa leaves include improving the immune system, reducing the risk of nutritional deficiencies, and support for digestive health. The main problem is that many people are not aware of the potential health benefits of Moringa leaves, which results in low consumption and utilization of this plant. The problem solving plan carried out is with the right communication approach. The benefits of Moringa leaves are very important. One effective strategy is through board games. The main aim is to provide education to parents who have an important role in integrating Moringa leaves into their daily diet as well as educating children about the importance of good nutrition. Through this board game, people can learn about the benefits of Moringa leaves directly, from their nutritional content to how to use them in everyday life.